Integrative Analysis of the DICER-like (DCL) Genes From Peach (Prunus persica): A Critical Role in Response to Drought Stress - Belal, Mohammad A.; Ezzat, Mohamed; Zhang, Yuanqiang; Xu, Ziang; Cao, Yunpeng; Han, Yuepeng (Frontiers in Ecology and Evolution, 2022)
DICER-likes (DCLs) proteins are the core component for non-coding RNA (ncRNA) biogenesis, playing a central role in RNA interference (RNAi). Our current knowledge about the DCL family is based on studies using the model plants, but little information is available in perennial fruit crops. Here, we reported the DCL gene family in Prunus persica and other four Rosaceae species, Fragaria vesca, Prunus mume, Malus × domestica, and Pyrus bretschneideri, with the latter two sharing a recent event of whole-genome duplication (WGD). Phylogenetic analysis revealed that DCL genes were divided into four clades, DCL1 - DCL4. Gene duplication and loss events were observed for the DCL gene family over a long period of evolutionary time. DCLs belonged to a small gene family and their expansion was mainly driven by WGD instead of tandem duplication. Gene expression profiling revealed that PpDCLs from P. persica had different expression patterns and they were differentially expressed under drought stress. Two PpDCL2 members, PpDCL2a and PpDCL2c, were found to be good candidates involved in the regulation of drought stress in peach. Our results presented here will be useful for better understanding the molecular evolution of DCL genes in plants, and for future functional analysis of PpDCLs in P. persica.